Quality assessment in Belgian arrhythmology: the Belgian heart rhythm association (BeHRA) databases. Issue 1 (2nd January 2019) - Mairesse, Georges H.; Le Polain de Waroux, Jean-Benoit; Willems, Rik; Aelvoet, Willem; Blankoff, Ivan; Vijgen, Johan; Verbeet, Thierry
Abstract: This report presents and discusses, on behalf of the Belgian College of Cardiology, the evolution of the peer review process in arrhythmology, focussing on pacemaker implantation. Data from the last 22 years are compared. The national annual increase in implants is around 1%, clinical patient characteristics remained stable over the years while dual chamber pacing was proportionally increasing. Analyses of the normalised sick sinus and complete atrioventricular block ratios revealed a quite homogenous practice between centres and patient district with the only exception of the two more crowded districts. Battery longevity and infection rate were also assessed. With an incidence of 1/1000 device-years follow-up, Belgium remains below accepted European levels.